2015
DOI: 10.1002/pds.3747
|View full text |Cite
|
Sign up to set email alerts
|

Quick assessment of drug-related admissions over time (QUADRAT study)

Abstract: Automated pre-selection of PP-ADEs is an efficient way to monitor crude trends. Further validation and manual assessment of the automatically selected hospitalizations is necessary to get a more detailed and precise picture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 17 publications
5
18
0
Order By: Relevance
“…The Quick Assessment of Drug-Related Admissions over Time (QUADRAT) study showed a decreasing trend of possible HARMs in The Netherlands between 2005 (4.65%) and 2008 (3.91%). 11 These results are comparable to findings in other Western countries. [13][14][15] The percentage of potentially preventable HARMs only showed a small decreasing trend in the QUADRAT study with 20.5% in 2005 and 18.4% in 2008.…”
Section: Introductionsupporting
confidence: 86%
See 3 more Smart Citations
“…The Quick Assessment of Drug-Related Admissions over Time (QUADRAT) study showed a decreasing trend of possible HARMs in The Netherlands between 2005 (4.65%) and 2008 (3.91%). 11 These results are comparable to findings in other Western countries. [13][14][15] The percentage of potentially preventable HARMs only showed a small decreasing trend in the QUADRAT study with 20.5% in 2005 and 18.4% in 2008.…”
Section: Introductionsupporting
confidence: 86%
“…The percentage of potentially preventable HARMs only showed a small decreasing trend in the QUADRAT study with 20.5% in 2005 and 18.4% in 2008 11 . This potential preventability was lower compared to the other Dutch studies which calculated a percentage of 29,0% and 46.0%.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…The Dutch guideline "Polypharmacy in the older patient" includes a trigger list that can be used to establish whether an admission is possibly medication related [62]. The trigger list is mainly based on three studies namely the HARM-, IPCI-and Quadret, and presents the most frequent medication related problems which can lead to an admission [7,11,63,64].…”
Section: Discussionmentioning
confidence: 99%